Pathophysiological role of endogenous irisin against tumorigenesis and metastasis: Is it a potential biomarker and therapeutic? - Dewan Md. Sumsuzzman; Yunho Jin; Jeonghyun Choi; Jeong-Hee Yu; Tae Ho Lee; Yonggeun Hong (Tumor Biology)
In the last few decades, there has been notable progress in understanding the molecular and cellular basis of the complex process involved in cancer. In this context, tumor-promoting inflammation, dysregulation of apoptotic signaling, tissue invasion and metastasis, and cancer microenvironment have recently attracted interest from researchers. Irisin is a hormone released by muscles during exercise and it directly acts on key functional cells involving energy metabolism and homeostasis. Recently, many studies have reported the anticancer effect of irisin against different types of cancer. Translation of these findings to clinical practice for the diagnosis and treatment of several types of cancer is urgently required. In this review, we summarized preclinical and clinical studies on the anticancer effects of irisin in various types of cancer, and also discussed the mechanisms activated by irisin to suppress cancer pathogenesis. We further discussed the serum level of irisin related to different types of cancer to understand more clearly the association between irisin concentration and tumor burden. This review may serve as a solid foundation for researchers and physicians to support basic and clinical studies on irisin as a promising strategy for early diagnosis and treatment of a various types of cancers.